Introduction. Neoliberalism and precarization of social conditions - Piedra Guillén, Nancy (2022)
In this volume of the Journal of Social Sciences we have wanted to allocate a specific section to analyze the impact that had in our country the development of neoliberalism. There's no doubt that that in a historical moment like the one we are living in the country, in which, with the electoral results that we have recently had, the neoliberal reform of the State and society is consolidated, it is more How opportune to spend time studying this topic. Therefore, we have compiled several texts that allow us to understand the model of development that has been applied, as well as its consequences, and thus better understand the socio-economic impacts that affect various sectors of society.